Energy efficiency of perennial herbaceous crops production depending on the type of digestate and mineral fertilizers. (1st September 2017) - Stolarski, Mariusz J.; Krzyżaniak, Michał; Warmiński, Kazimierz; Tworkowski, Józef; Szczukowski, Stefan; Olba–Zięty, Ewelina; Gołaszewski, Janusz
Abstract: The aim of this study was to analyse the input and energy efficiency of the biomass production of four species of Perennial Herbaceous Crops (PHC): Helianthus tuberosus, Sida hermaphrodita, Helianthus salicifolius, Miscanthus × giganteus . The crops were fertilised with three types of biogas plant digestate (wet digestate, dry digestate, torrefied digestate) and mineral fertilizers at two rates (85 and 170 kg ha −1 N). Analyses for the study were based on average values of the three years of the experiment (2013–2015) conducted in north-eastern Poland. The total energy input ranged widely (2832–59, 080 MJ ha −1 ), depending on the species, forms and level of fertilisation. The lowest input was observed at control sites. The highest input was recorded where torrefied and dry digestate were used as fertilisers, which was a consequence of the high energy intensity of their production. Helianthus salicifolius gave the highest energy gain of all the fertilisation options and in the control plot compared to the other three PHC species. The highest energy efficiency ratio in the experiment (19.1) was obtained for Helianthus salicifolius in the no-fertilisation option. Its values for the other species in the control plots were between 5 and 52% lower. Highlights: The total energy input ranged widely from 2.83 to 59.08 GJ ha −1 . The highest energy gain was for Helianthus salicifolius (139.6 GJ ha −1 year −1 ). Better energy efficiency ratios for all species were at the control plots. The highest energy ratio (19.1) was obtained for Helianthus salicifolius. Fertilisers resulted in lower energy efficiency of crops production.